Effect of steeping temperature on antioxidant and inhibitory activities of green tea extracts against α-amylase, α-glucosidase and intestinal glucose uptake. (1st November 2017) - Liu, Shuyuan; Ai, Zeyi; Qu, Fengfeng; Chen, Yuqiong; Ni, Dejiang
Highlights: Steeping temperature affects the main composition of green tea infusions. Green tea steeped at 100 °C shows the highest antioxidant activity. It also exhibits the highest α-amylase and α-glucosidase inhibitory activities. Green tea steeped at 60 °C shows the highest glucose uptake inhibition. Abstract: The objective of the present study was to evaluate the effect of steeping temperature on the biological activities of green tea, including the 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging capacity, α-glucosidase and α-amylase inhibitory activities, and glucose uptake inhibitory activity in Caco-2 cells. Results showed that, with increasing extraction temperature, the polyphenol content increased, which contributed to enhance antioxidant activity and inhibitory effects on α-glucosidase and α-amylase. Green tea steeped at 100 °C showed the highest DPPH radical-scavenging activity and inhibitory effects on α-glucosidase and α-amylase activities with EC50 or IC50 values of 6.15 μg/mL, 0.09 mg/mL, and 6.31 mg/mL, respectively. However, the inhibitory potential on glucose uptake did not show an upward trend with increasing extraction temperature. Green tea steeped at 60 °C had significantly stronger glucose uptake inhibitory activity ( p < 0.05). The integrated data suggested that steeping temperature should be considered when evaluating the biological activities of green tea.